Pulmonoprotective effect of carnosol on LPS-induced cytokine storm model in mice - Abed Mansoor, Ahmed F.; Abu-Raghif, Ahmed Rahmah; Ridha-Salman, Hayder; Al-Asady, Furqan Mohammed; Shleghm, Maytham Razaq; Hussein, Muataz Naeem (European Journal of Clinical and Experimental Medicine, 2026)
Introduction and aim. The cytokine storm represents a severe hyperinflammatory response that can lead to acute lung injury and organ failure. Carnosol, a phenolic diterpene derived from Rosmarinus officinalis, exhibits documented antioxidant and anti-inflammatory properties. The aim was to evaluate the effects of carnosol, alone and in combination with methylprednisolone acetate (MPA), in a lipopolysaccharide (LPS)-induced cytokine storm model in mice. Material and methods. Sixty male mice were randomly assigned to six groups: control, lipopolysaccharide (LPS), vehicle, carnosol (120 mg/kg), methylprednisolone acetate (50 mg/kg), and combined carnosol plus methylprednisolone acetate (half doses). Treatments were administered for seven days following LPS induction. Pulmonary concentrations of interleukin-1 beta (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor alpha (TNF-α) were quantified using enzyme-linked immunosorbent assay, and lung histopathology was evaluated. Results. Lipopolysaccharide administration significantly increased pulmonary cytokine levels compared with controls (IL-1β: 85.8±13.5 vs. 11.5±3.8 pg/g; IL-6: 93.0±8.5 vs.16.6±4.8 pg/g; TNF-α: 144.4±10.1 vs.18.6±0.01 pg/g; all p<0.05). Treatment with carnosol significantly reduced IL-1β, IL-6, and TNF-α levels compared with the LPS group (p<0.05). The combined carnosol and methylprednisolone acetate therapy produced the greatest cytokine attenuation (e.g. IL-6: 24.6±1.8 pg/g vs. LPS; p<0.05) and was associated with the most pronounced improvement in lung histopathological scores (p<0.05). Conclusion. Carnosol attenuates lipopolysaccharide-induced pulmonary inflammation and cytokine overproduction in a murine model. Its combination with methylprednisolone acetate may enhance anti-inflammatory efficacy and allow for glucocorticoid dose reduction. These findings provide preclinical evidence supporting further mechanistic and translational studies.